2013
DOI: 10.1016/j.bone.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different screening tools (FRAX®, OST, ORAI, OSIRIS, SCORE and age alone) to identify women with increased risk of fracture. A population-based prospective study

Abstract: Comparison of FRAX® and simpler screening tools (OST, ORAI, OSIRIS, SCORE) in predicting fractures indicate that FRAX® did not perform better in fracture risk prediction compared with the simpler tools or even age alone in a screening scenario without bone mineral density assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 42 publications
5
46
1
1
Order By: Relevance
“…The study by Pecina et al (8) showed that the sensitivity and AUC were 36% and 55% respectively for FRAX, 74% and 58% for SCORE, 56% and 63% for OST, and 52% and 60% for ORAI. (8) The study by Rubin et al, (10) comparing FRAX and other tools, found that the performance of FRAX and the other tools were not much different, with the AUC ranging between 70.3%-72.2%. (10) These studies have demonstrated that the increase in added risk factors in these tools did not add to the performance in evaluating the risk of low bone mass.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Pecina et al (8) showed that the sensitivity and AUC were 36% and 55% respectively for FRAX, 74% and 58% for SCORE, 56% and 63% for OST, and 52% and 60% for ORAI. (8) The study by Rubin et al, (10) comparing FRAX and other tools, found that the performance of FRAX and the other tools were not much different, with the AUC ranging between 70.3%-72.2%. (10) These studies have demonstrated that the increase in added risk factors in these tools did not add to the performance in evaluating the risk of low bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…(8) The study by Rubin et al, (10) comparing FRAX and other tools, found that the performance of FRAX and the other tools were not much different, with the AUC ranging between 70.3%-72.2%. (10) These studies have demonstrated that the increase in added risk factors in these tools did not add to the performance in evaluating the risk of low bone mass. Age and body weight are the most influential risk factors for osteoporosis (4,5,19) so that the other factors added to these screening tools could not much increase their performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations